2014
DOI: 10.4161/sgtp.29019
|View full text |Cite
|
Sign up to set email alerts
|

Rho GTPases modulate malignant transformation of tumor cells

Abstract: Rho GTPases are involved in the acquisition of all the hallmarks of cancer, which comprise 6 biological capabilities acquired during the development of human tumors. The hallmarks include proliferative signaling, evading growth suppressors, resisting cell death, enabling replicative immortality, inducing angiogenesis, and activating invasion and metastasis programs, as defined by Hanahan and Weinberg. (1) Controlling these hallmarks are genome instability and inflammation. Emerging hallmarks are reprogramming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
161
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(165 citation statements)
references
References 238 publications
(250 reference statements)
1
161
0
3
Order By: Relevance
“…Note that we cannot completely rule out that potential mutations in Rac1 and Cdc42 could also impact their activity in human PCC. Indeed, several recent studies reported point mutations in Rho-GTPases as driver mutations in various types of cancer, including melanoma, lymphoma, breast, lung, and head and neck cancers (for review see Alan &Lundquist 2013 andOrgaz et al 2014). However, none of these studies reported mutations leading to inactivation of the Rac1 or Cdc42 GTPase.…”
Section: :4mentioning
confidence: 99%
See 1 more Smart Citation
“…Note that we cannot completely rule out that potential mutations in Rac1 and Cdc42 could also impact their activity in human PCC. Indeed, several recent studies reported point mutations in Rho-GTPases as driver mutations in various types of cancer, including melanoma, lymphoma, breast, lung, and head and neck cancers (for review see Alan &Lundquist 2013 andOrgaz et al 2014). However, none of these studies reported mutations leading to inactivation of the Rac1 or Cdc42 GTPase.…”
Section: :4mentioning
confidence: 99%
“…Consequently, Rho GTPases have been largely implicated in many types of cancer, and numerous studies have shown that aberrant expression of Rho GTPases is associated with tumor growth, invasion, and metastasis. The evidence for the role of Rho GTPases in various stages of tumorigenesis has been compiled in comprehensive reviews (Ellenbroek & Collard 2007, Grise et al 2009, Karlsson et al 2009, Parri & Chiarugi 2010, Alan & Lundquist 2013, Orgaz et al 2014). However, the expression level of Rho GTPase genes or proteins does not necessarily reflect their activation state.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] Therefore, Rho GTPase signaling has been involved in many aspects of cancer biology, from tumor initiation to tumor cell proliferation, invasion and metastasis. 6,7 How Rho GTPases are modulated in tumor is currently a major and a challenging issue. Most studies have monitored the expression levels of Rho GTPases in human cancer and several of them have been found overexpressed.…”
mentioning
confidence: 99%
“…The Rac proteins (Rac1, Rac2, and Rac3) are a subgroup of the Rho-GTPase family that regulate cell motility and, when deregulated, drive cancer invasion and metastasis (1)(2)(3). Rac proteins undergo rapid and spatiotemporally coordinated cycles of activation and inactivation linked to upstream receptor signaling by guanine nucleotide exchange factors (GEFs) 2 (4).…”
Section: Waf1/cip1mentioning
confidence: 99%
“…relative to control shRNA, which was assigned an arbitrary value of 1 (n ϭ 3). C, quantitative RT-PCR analysis of PREX1 mRNA normalized to GAPDH from MCF-7-luc-F5 cells stably expressing control shRNA, PREX1 shRNA (1), or PREX1 shRNA (2). Data are presented as mean -fold difference Ϯ S.E.…”
Section: Prex1 Regulates Cell Proliferation and Cyclin D1 And P21mentioning
confidence: 99%